2002
DOI: 10.1182/blood.v100.4.1425.h81602001425_1425_1429
|View full text |Cite
|
Sign up to set email alerts
|

Clonal relation in a case of CLL, ALCL, and Hodgkin composite lymphoma

Abstract: Large cell lymphomas and Hodgkin disease may develop during the course of chronic lymphocytic leukemia (CLL). In some cases the transformed cells are Epstein-Barr virus (EBV)–positive and not clonally related to the CLL cells. In other cases the transformed cells have the same clonal rearrangements as the CLL cells. Here we describe a composite lymphoma in a patient with CLL that exhibits a combination of CLL/small lymphocytic lymphoma, large cell lymphoma with anaplastic morphology, and Hodgkin lymphoma (HL).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 20 publications
0
38
0
1
Order By: Relevance
“…Histologically, the two lymphoma populations, although exhibiting a markedly different morphology and immunophenotype, were intermingled to a degree not seen in the previous CL. [3][4][5][6][7][8]28,29 In particular, at a first glance this case appeared as a cHL of the lymphocyte-rich subtype, 39 because typical HRS cells (sometimes rosetted by T cells) were embedded in a somewhat nodular cellular background composed of apparently normal, expanded mantle zones. It was only after performing a cyclin D1 staining (prompted by the clinical history of the patient) that the neoplastic nature of the mantle zone B cells became evident.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Histologically, the two lymphoma populations, although exhibiting a markedly different morphology and immunophenotype, were intermingled to a degree not seen in the previous CL. [3][4][5][6][7][8]28,29 In particular, at a first glance this case appeared as a cHL of the lymphocyte-rich subtype, 39 because typical HRS cells (sometimes rosetted by T cells) were embedded in a somewhat nodular cellular background composed of apparently normal, expanded mantle zones. It was only after performing a cyclin D1 staining (prompted by the clinical history of the patient) that the neoplastic nature of the mantle zone B cells became evident.…”
Section: Discussionmentioning
confidence: 93%
“…5 For mutation analysis, samples after WGA of both lymphoma types were used. 6 The NOTCH1 analysis consistently detected a known single nucleotide polymorphism (rs2229974) at DNA position 53603 of NG_007458.1 with homozygous genotype (T/T) in exon 34. 7 Likely occurred independently in the HRS and MCL cells.…”
Section: Cdkn2a-b/9p21mentioning
confidence: 93%
See 1 more Smart Citation
“…into the development of those composite lymphomas were provided by single cell PCR analysis for rearrranged Ig V genes of the two lymphomas. Thus, clonal relationship between the two different tumours was demonstrated in the majority of the cases analysed (13)(14)(15)(16)(17)(18)(19)(20). Interestingly, in many of the clonally related cases, the rearranged V genes of the two lymphomas showed both shared as well as distinct somatic mutations in the HRS and the NHL cells.…”
Section: Pathogenesis Of Composite Lymphomasmentioning
confidence: 92%
“…Molecular analysis of rare cases of bigenotypic and biphenotypic, t(14;18)-positive lymphomas showed that two distinct neoplastic B-cell clones may be derived from a single progenitor cell (Cleary et al, 1988). Another study of a composite lymphoma also revealed a common genetic abnormality that was found in three different lymphomatous components (van de Berg et al, 2002). The presence of a dormant lymphoma progenitor cell may explain why FL, a (2006) reported on the molecular characterisation of a large number of patients suffering from pyruvate kinase (PK) deficiency.…”
mentioning
confidence: 99%